Islam and Christianity in the Horn of Africa: Somalia, Ethiopia, Sudan - Erlikh, Ḥagai (Lynne Rienner Publishers, 2010)
Muslims and Christians in the horn of Africa : interactions across the centuries -- From disastrous confrontation to pragmatic friendship : Ethiopia and Sudan, 1884-1898 -- Radicalism, war, and pragmatism : Ethiopia and the Somalis, 1899-1920 -- Africanism, Arabism, and Marxism : Ethiopia and Sudan, 1930-1991 -- The return of political Islam : Ethiopia and Sudan, 1991-2009 -- Nationalism and conflict : Ethiopia and Somalia, 1943-1991 -- Religion returns to the forefront : Ethiopia and Somalia, 1991-2009 -- Religion and politics in the horn : options and choices